Viability of the Antitrust Per Se Illegality Rule: Schwinn Down, How Many to Go? - William S. Stewart; Barry S. Roberts (Washington University Law Quarterly, 1980)
The impact of Sylvania on various antitrust restraints is first examined in a descriptive fashion. Then, a principled approach for dealing generally with this type of econo-legal problem is suggested.
Keywords: Continental Television; Inc. v. GTE Sylvania; Inc. 433 U.S. 36 (1977); Antitrust law; Price fixing; Restraint of trade; United States